Teaching System, Education Curriculum, and Education Quality Strategy in Pondok Pesantren Lirboyo Kediri City - Junaidi, Kholid (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2019)
This article aims to describe the teaching system, education curriculum, and strategies for improving the quality of education in Lirboyo Islamic Boarding School in Kediri. This article was written using a qualitative descriptive method, which is a research procedure that produces data in the form of written and oral words of the person being investigated. The result is showing that the teaching system at Lirboyo Islamic Boarding School is divided into two, namely the classical learning system and the non-classical learning system. The classical learning system was adopted from the modern education system, namely the santri grouped according to a class level according to their ability level. Madrasah IbtidÄâ€™iyah level, Tsanawiyah level (Mts), â€˜Aliyah level (MA), or Iâ€˜dÄdiyah level (SP). The other hand, the non-classical learning systems are directly guided by the kiai with the sorogan and bandongan methods. The education curriculum at Lirboyo Islamic Boarding School is broadly divided into seven groups of Subjects of Jurisprudence, HadÄ«th, Alquran, Monotheism, Arabic Literature, Sufism, Alquran Interpretation. It can be concluded, the curriculum at the Lirboyo boarding school is still closely related to the salaf (traditional) curriculum. Meanwhile, one of the strategies to improve the education quality in Lirboyo Islamic Boarding School is by evaluating the learning outcomes through MuhÄfazah akhÄ«r al-Sanah at the end of the year and improve the graduation criteria from year to year. When announcing the results of MuhÄfazah, the elders (mashÄyikh) witnessing it, so that the mudÄ«r was motivated to improve the education quality of their students",